Determinants of health care utilisation: the case of Timor-Leste. Issue 6 (11th July 2018) - Guinness, Lorna; Paul, Repon C; Martins, Joao S; Asante, Auguste; Price, Jennifer A; Hayen, Andrew; Jan, Stephen; Soares, Ana; Wiseman, Virginia
Abstract: Background: Health financing and delivery reforms designed to achieve universal health coverage (UHC) need to be informed by an understanding of factors that both promote access to health care and undermine it. This study examines the level of health care utilisation in Timor-Leste and the factors that drive it. Methods: Data from a nationally representative cross-sectional survey of health care utilisation in 1712 households were used to develop multilevel models exploring how need and predisposing and enabling factors explain health care utilisation at both primary and secondary care facilities. Results: Need was found to be the key driver in seeking both primary care and hospital services. Rural households were less likely to go to hospital (odds ratio 0.7) than urban households. The poorest quintile was also less likely to use more expensive hospital services than other socio-economic groups. Conclusions: Understanding the determinants of seeking health care in Timor-Leste is of considerable policy significance, because health care is free at the point of use. Our findings indicate that the public resources for health care are subsidising the rich more than the poor. Health care reforms in Timor-Leste need to reduce the 'other' costs of health care, such as distance barriers, to address these inequities.